2015
DOI: 10.4314/ijmu.v10i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Study on the attitude of “Tomorrow’s Doctors” towards mental illness: A cross-sectional study

Abstract: Different studies show different attitudes towards mental illness among medical students. This study was initiated to explore the attitude towards mental illness among medical students in a medical college of Manipur. A cross-sectional selfadministered questionnaire-based study was conducted among medical students in Manipur. Two self rating scales -Social Distance Scale and Dangerousness scale were used to assess attitude towards mental illness. Descriptive statistics and independent sample t-test were applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…These 􀅫indings are consistent with prior research on the subject by Bista (2016); Munnawar and Awan (2019); J. Singh (2015). In his doctoral study Majeed (2024) reported that stakeholders generally agree that the semester system effectively develops various student skills and abilities, but satisfaction levels vary.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These 􀅫indings are consistent with prior research on the subject by Bista (2016); Munnawar and Awan (2019); J. Singh (2015). In his doctoral study Majeed (2024) reported that stakeholders generally agree that the semester system effectively develops various student skills and abilities, but satisfaction levels vary.…”
Section: Discussionsupporting
confidence: 86%
“…J. Singh (2015) discovered that students hold varied opinions about the semester system. Although it focuses on the student and is credit-based, a detailed schedule, calendar, and timely results are essential for effective implementation.…”
Section: Literature Reviewmentioning
confidence: 99%